2013
DOI: 10.1186/1756-0500-6-373
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for resistant hypertension among hypertensive patients from a developing country

Abstract: BackgroundTo study the prevalence and define deferential risk factors for ‘Resistant’ hypertension (RHT) in a hypertensive population of South Asian origin.MethodsA descriptive cross-sectional study was carried out among hypertensive patients attending clinics at the Cardiology Unit, Colombo from July-October 2009. All the patients with hypertension who provided informed written consent were recruited to the study (n = 277). A pre-tested interviewer-administered questionnaire was used for data collection. A bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
24
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 41 publications
11
24
1
1
Order By: Relevance
“…Previous epidemiologic studies indicated that the prevalence of RH among hypertensive population ranges from 10% to 30% [10]. Many studies reported that diabetes was a significant risk factor of RH occurrence among hypertensive patients [10,[12][13][14][15][16][17][18][19][20][21]. In comparing the results of this study with others which were conducted among hypertensive patients without type 2 diabetes, the prevalence of RH was higher.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Previous epidemiologic studies indicated that the prevalence of RH among hypertensive population ranges from 10% to 30% [10]. Many studies reported that diabetes was a significant risk factor of RH occurrence among hypertensive patients [10,[12][13][14][15][16][17][18][19][20][21]. In comparing the results of this study with others which were conducted among hypertensive patients without type 2 diabetes, the prevalence of RH was higher.…”
Section: Discussionsupporting
confidence: 51%
“…This result was consistent with several studies among hypertensive patients with or without diabetes. A Colombian study reported that increasing in age increased the risk to have RH (OR: 1.36) [13]. Besides, a study conducted in Japan showed that increasing age is significantly associated with RH (P < 0.05) [19].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…32,33 Ascertaining the risk factors of hypertension could provide significant information for the prevention of hypertension and cardiovascular diseases. 34 In this meta-analysis, we quantitatively assessed the associations between shortterm and long-term exposure to ambient air pollutants and the risk of hypertension. We observed that short-term exposure to SO 2 , PM 2.5 , and PM 10 and long-term exposure to NO 2 and PM 10 were associated with an increase in hypertension risk.…”
Section: Discussionmentioning
confidence: 99%